Cartilage, Synovium and Bone 2018
DOI: 10.1136/annrheumdis-2018-eular.7038
|View full text |Cite
|
Sign up to set email alerts
|

AB0090 Verbascoside and hydroxytyrosol downregulate stress-related pathways in human osteoarthritic articular chondrocytes

Abstract: BackgroundOsteoarthritis (OA), is a leading cause of joint dysfunction and the disease is characterised by progressive destruction of the articular cartilage.1 At the molecular level, degeneration of the cartilage is attributed to multifactorial events including oxidative stress, mitochondrial dysfunction, apoptosis and associated changes in inflammatory and catabolic gene expression.2 Recent studies have revealed the essential role of plant-derived antioxidants in preventing pathophysiological events observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 3 publications
2
6
0
Order By: Relevance
“…In accordance with the findings of our preliminary studies (Elmazoglu et al, 2018(Elmazoglu et al, , 2020Goker et al, 2018) and other laboratories (Charlier et al, 2016;Hardin et al, 2015;Lepetsos et al, 2019;Portal-Nunez et al, 2016) (Lepetsos et al, 2019;Sun et al, 2017). In the present study, OACs at p0-1 showed a higher pJNK/JNK ratio and excessive ROS production than OACs at p2-3<, supporting the notion that the interaction between ROS and JNK plays a distinctive role in OA pathology.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In accordance with the findings of our preliminary studies (Elmazoglu et al, 2018(Elmazoglu et al, , 2020Goker et al, 2018) and other laboratories (Charlier et al, 2016;Hardin et al, 2015;Lepetsos et al, 2019;Portal-Nunez et al, 2016) (Lepetsos et al, 2019;Sun et al, 2017). In the present study, OACs at p0-1 showed a higher pJNK/JNK ratio and excessive ROS production than OACs at p2-3<, supporting the notion that the interaction between ROS and JNK plays a distinctive role in OA pathology.…”
Section: Discussionsupporting
confidence: 92%
“…The microelectronic biosensor iCELLigence Real Time Cell Analysis System® (RTCA, ACEA Biosciences, San Diego, CA, USA) was used to measure impedance when cells adhere to the microelectrodes causing an alternating current (Elmazoglu et al, 2018(Elmazoglu et al, , 2020. This new concept has just emerged as an interesting method based on the use of culture plates (E-Plates) with gold microelectrodes in their base.…”
Section: Measurement Of Cell Impedance By Icelligencementioning
confidence: 99%
See 1 more Smart Citation
“…After biologics treatment, Rooney's score in RL group and M group were 10. 4 4 The alterations in cell counts, viability (MTT, NRU), proliferation (RTCA-iCELLigence System), reactive oxygen species (ROS) generation, stress-related signalling proteins and inflammatory progenitors ICE/caspase-1 (ELISA) were determined. Results: Cell viability was increased at lower concentrations of hydroxytyrosol in OA chondrocytes (P1, 30th day).…”
Section: Discussionmentioning
confidence: 99%
“…İSM.4.06.68.49), as described previously. 4 The alterations in cell counts, viability (MTT, NRU), proliferation (RTCA-iCELLigence System), reactive oxygen species (ROS) generation, stress-related signalling proteins and inflammatory progenitors ICE/caspase-1 (ELISA) were determined. Results: Cell viability was increased at lower concentrations of hydroxytyrosol in OA chondrocytes (P1, 30th day).…”
Section: Discussionmentioning
confidence: 99%